2017
DOI: 10.1002/anie.201701288
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport with Ultralow Friction through Partially Exfoliated g‐C3N4 Nanosheet Membranes with Self‐Supporting Spacers

Abstract: Two-dimensional (2D) graphitic carbon nitride (g-C N ) nanosheets show brilliant application potential in numerous fields. Herein, a membrane with artificial nanopores and self-supporting spacers was fabricated by assembly of 2D g-C N nanosheets in a stack with elaborate structures. In water purification the g-C N membrane shows a better separation performance than commercial membranes. The g-C N membrane has a water permeance of 29 L m h bar and a rejection rate of 87 % for 3 nm molecules with a membrane thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
156
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(161 citation statements)
references
References 53 publications
2
156
1
2
Order By: Relevance
“…[8] Recently,G eim et al described the ions transportation properties through angstrom-scale graphene slits. [10] Meanwhile,m embrane materials and methods based on carbon nitride have been developed to realize water transport, [11] actuators, [12] and separation, [13] all questions closely related to the present work. [6] Tw od imensional carbon nitride (C 3 N 4 ) materials are another obvious choice with inherent lateral porosity,and it already attracting broad interest with its broad applications in sensing,b io-imaging,n ovel solar energy exploitation, as well as photocatalysis.…”
mentioning
confidence: 82%
“…[8] Recently,G eim et al described the ions transportation properties through angstrom-scale graphene slits. [10] Meanwhile,m embrane materials and methods based on carbon nitride have been developed to realize water transport, [11] actuators, [12] and separation, [13] all questions closely related to the present work. [6] Tw od imensional carbon nitride (C 3 N 4 ) materials are another obvious choice with inherent lateral porosity,and it already attracting broad interest with its broad applications in sensing,b io-imaging,n ovel solar energy exploitation, as well as photocatalysis.…”
mentioning
confidence: 82%
“…[2,8] As calculated by this equation (Supporting Information, Note S4), MXene-230 yields the permeance of 1.3 10 À4 Lm À2 h À1 bar À1 for water and of 4.3 10 À4 Lm À2 h À1 bar À1 for acetone,s even orders of magnitude smaller than the experimental values.D ynamics simulations have shown that in confined space,p olar molecules adopt concerted orientations by forming intermolecular bonds. [2,8] As calculated by this equation (Supporting Information, Note S4), MXene-230 yields the permeance of 1.3 10 À4 Lm À2 h À1 bar À1 for water and of 4.3 10 À4 Lm À2 h À1 bar À1 for acetone,s even orders of magnitude smaller than the experimental values.D ynamics simulations have shown that in confined space,p olar molecules adopt concerted orientations by forming intermolecular bonds.…”
mentioning
confidence: 87%
“…The K' value for MXene membrane (10 À8.5 )isover five orders of magnitude higher than that of GO membrane (10 À13.8 ), highlighting an ultralow transport barrier through MXene channels.C onsidering as harp decline in water permeance even after small disturbance of water-bonded flow, [4] these regular and straight channels have proven to be the most efficient transfer pathways to assure low-barrier molecular transfer. [5] As summarized in Figure 3dand the Supporting Information, Table S1, the MXene membrane exhibits an exceptional water separation performance,w hich outperforms almost all of the lamellar membranes including GO, WS 2 ,and MoS 2 , [2,15] highlighting the superiority of regular and straight transport channels. This observation can also be confirmed by the boosted K' value (10 À12.6 )o fG Om embrane when improving channel regularity (Supporting Information, Figure S23).…”
mentioning
confidence: 97%
“…[9] Searching for porous nanosheets to fabricate 2D laminates may be an alternative way to accomplish higher permeances,b ecause pores can offer additional routes for mass transport. [12] However, the resulting g-C 3 N 4 lamellar membrane only shows amoderate water flux of 29 Lh À1 m À2 bar À1 , which is even lower than those of 2D membranes stacked by dense nanosheets.W ec onsidered the narrow interlayer spacing with as ize of 0.32 nm in g-C 3 N 4 membranes is adverse for rapid water penetration. [11] In view of g-C 3 N 4 layered structures and porosity,W ang et al successfully assembled them into 2D membranes,a nd they discovered the water transport through the g-C 3 N 4 membrane occurred with ultralow friction, similar to water passing through graphene interlayers.…”
mentioning
confidence: 92%